Suggestions for the promotion of evidence-based public health in South Korea - Bae, Jong-Myon (Epidemiol Health, 2017)
Evidence-based public health (EBPH) is defined as public health decision-making based on current best evidence. Debates about the latent tuberculosis infection control program suggested by the Korea Centers for Disease Control and Prevention in 2017 highlight the need to promote EBPH. Three strategies have been proposed, including providing necessary evidence by evaluating policy-evidence gaps; delivering high-quality, relevant, and timely evidence by conducting systematic reviews and adapting public health guidelines; and making value-driven decisions by training and educating public health policymakers.